Management of endoscopic retrograde cholangiopancreatography-related perforations - Kim, Byung Seup (The Korean Surgical Society, 2011)
PURPOSE: The purpose of this study is to analyze the treatment strategies of patients with endoscopic retrograde cholangiopancreatography (ERCP)-related perforations. This is a retrospective study. METHODS: We experienced 13 perforations associated with ERCP. We reviewed the medical recordsand classified ERCP-related perforations according to mechanism of injury in terms of perforating device. Injury by endoscopic tip or insertion tube was classified as type I, injury by cannulation catheter or sphincterotomy knife as type II, and injury by guidewire as type III. RESULTS: Of four type I injuries, one case was managed by conservative management after primary closure with a hemoclip during ERCP. The other three patients underwent surgical treatments such as primary closure orpancreatico-duodenectomy. Of five type II injuries, two patients underwent conservative management and the other three cases were managed by surgical treatment such as duodenojejunostomy, duodenal diverticulization and pancreatico-duodenectomy. Of four type III injuries, three patients were managed conservatively and the remaining patient was managed by T-tube choledochostomy. CONCLUSION: Type I injuries require immediate surgical management after EPCP or immediate endoscopic closure during ERCP whenever possible. Type II injuries require surgical or conservative treatment according to intra- and retro-peritoneal dirty fluid collection findings following radiologic evaluation. Type III injuries almost always improve after conservative treatment with endoscopic nasobilliary drainage.